PELATIHAN PEMBUATAN DAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS MOBILE LEARNING MENGGUNAKAN APLIKASI “RUMAH BELAJAR” - Agus Setiawan; Muhyidin Thohir; Asriatul Jannah (JPM PAMBUDI, 2022)
Technological developments have had a major impact on education so that educators must prepare themselves to develop processes and use of instructional media as the main means of supporting learning. The purpose of this study is to train teachers to be able to use Learning Houses as a technology-based platform that can be used as a learning medium. This service method uses the Assed Based Communities Development (ABCD) approach with community service steps, namely discovery, dream, design, define, destiny. Assisted subjects are IPPNU members. The assisted result is that the assisted subjects of IPPNU members are able to use, design and utilize the Learning House platform so that it can be used as an alternative free learning media.